2019
DOI: 10.21203/rs.2.17553/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome analysis reveals differential immune related genes expression in Ruditapes philippinarum under hypoxia stress: Potential HIF and NF-κB crosstalk in immune responses in clam

Abstract: Background: Hypoxia is an important environmental stressor in aquatic ecosystems, with increasingly impacts on global biodiversity. Benthic communities are the most sensitive parts of the coastal ecosystem to eutrophication and resulting hypoxia. As a filter-feeding organism living in the seafloor sediment, Ruditapes philippinarum represents an excellent "sentinel" species to assess the quality of marine environment. In order to gain insight into the molecular response and acclimatization mechanisms to hypoxia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…We saw an increase in expression of Fibropellin-1 in the bearded fireworm after the second hypoxic timepoint in the intermittent hypoxia trial (over 18 h after initial hypoxic exposure) which corresponds well with the clam’s drastic increase in this gene after 2 days of chronic hypoxia. However, it is important to note that a significant decrease in expression of Fibropellin-1 was seen after 5 and 8 days in the clam 81 . During our chronic hypoxia exposure experiment, we were only able to sample after 7 days, so we may have missed this spike in expression, but our intermittent experiment allows us to see a similar response.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We saw an increase in expression of Fibropellin-1 in the bearded fireworm after the second hypoxic timepoint in the intermittent hypoxia trial (over 18 h after initial hypoxic exposure) which corresponds well with the clam’s drastic increase in this gene after 2 days of chronic hypoxia. However, it is important to note that a significant decrease in expression of Fibropellin-1 was seen after 5 and 8 days in the clam 81 . During our chronic hypoxia exposure experiment, we were only able to sample after 7 days, so we may have missed this spike in expression, but our intermittent experiment allows us to see a similar response.…”
Section: Discussionmentioning
confidence: 93%
“…Fibropellin-1, related to Notch protein-binding, was recently shown to have drastically increased in expression post chronic hypoxia in the clam Ruditapes philippinarum 81 . In the current study, we see a similar expression pattern in the intermittent but not chronic hypoxia trial.…”
Section: Discussionmentioning
confidence: 99%
“…The TolB-like protein, involved in a tol-dependent translocation system (Carr et al, 2000). The RING finger protein 170, which mediates the ubiquitination and degradation of inositol 1,4,5-trisphosphate receptors, and it is involved in immune response functions (Song et al, 2019) and finally, Fibropellin, a cell adhesion protein (Nie et al, 2020). Only a limited number of gene clusters appear to be under positive selection amongst those commonly used in immunity, stress response and shell formation comparative studies (in green), and the majority of the genes clusters showed negative selection with the exception of four, which resulted to be all involved in immune response pathways (Gerdol and Venier, 2015).…”
Section: Identification and Functional Analysis Of Positively Selected Genesmentioning
confidence: 99%